Tactics, techniques and team selection for K4 boats - Cobos Tellez, J.; Sanchez Hernandez, J. L.; Imaz, X. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
A maximum of 10 countries qualify for the Olympics. These 10 countries must be part of at least 3 continents. This selection was determined during the 2011 Szeged World Cup. The different 1000m competitions during the Olympics take place on separate days for each different category. The K4 1000m competition is on different day than the K1 and K2 competitions, creating the possibility that the best K1 and K2 of each country could participate in the K4 teams. There is a K4 REINFORCEMENT that allows K4 to become the main objective for the powerful teams in the 2011 World Cup. The qualifying competition for the 2011 World Cup was so demanding that countries like FRA, 1 st in the 2010 World Cup, BLR, 1 st in the 2008 Olympics, POR, 1st in the 2012 Europe Cup, failed to qualify for the Olympics. Instead FIUN qualified, despite a 2011 season in which they had trouble finding a crew guaranteed to qualify.